Comparative evaluation of antimicrobial activity of hydroalcoholic extract of Aloe vera, garlic, and 5% sodium hypochlorite as root canal irrigants against Enterococcus faecalis: An in vitro study - Swati Ramesh Karkare; Nivedita Pramod Ahire; Smita Uday Khedkar (Wolters Kluwer Medknow Publications, 2015)
Introduction: Enterococcus faecalis are the most resistant and predominant microorganisms recovered from root canals of teeth where previous treatment has failed. Over the past decade, interest in drugs derived from medicinal plants has markedly increased. In dentistry, phytomedicines has been used as an anti-inflammatory, antibiotic, analgesic, sedative, and also as an endodontic irrigant. In endodontics, because of the cytotoxic reactions of most of the commercial intracanal medicaments and their inability to eliminate bacteria completely from dentinal tubules, the trend is shifting toward use of biologic medication extracted from natural plants. Aim: To compare the antimicrobial efficacy of newer irrigating agents which would probably be as effective or more and at the same time less irritating to the tissues than sodium hypochlorite (NaOCl). The objective of this study was to compare the antimicrobial activity of saturated and diluted (1:1) hydroalcoholic extract of Aloe vera, garlic, and 5% NaOCl against E. faecalis using the commonly used agar diffusion method. Results: Saturated hydroalcoholic extract of A. vera showed the highest zone of inhibition against E. faecalis. NaOCl, which is considered as gold standard, also showed higher zones of inhibition.